A New Threshold Voltage and Drain Current Model for Lightly/Heavily Doped Surrounding Gate MOSFETs - Dutta, Pradipta (2016)
In this paper, we have presented a surface potential based drain current and threshold voltage model for surrounding gate MOSFETs that is valid for all doping concentrations. The Newton Raphson iterative technique is implemented for calculation of the potential at the surface and center of the channel and the drain current is then computed. The relative error between the potential values obtained from model and TCAD is within 2%. The drain current based on first iteration is much more accurate than the full depletion approximation. In the final part of this work, the threshold voltage is modeled based on two dimensional Poisson’s equation and the variation with channel radius is explored. A good match with reference data is observed.